GVHD Prophylaxis 2020 - Gooptu, Mahasweta; Antin, Joseph Harry (Frontiers in Immunology, 2021)
Graft-versus host disease (GVHD), both acute and chronic are among the chief non-relapse complications of allogeneic transplantation which still cause substantial morbidity and mortality despite significant advances in supportive care over the last few decades. The prevention of GVHD therefore remains critical to the success of allogeneic transplantation. In this review we briefly discuss the pathophysiology and immunobiology of GVHD and the current standards in the field which remain centred around calcineurin inhibitors. We then discuss important translational advances in GVHD prophylaxis, approaching these various platforms from a mechanistic standpoint based on the pathophysiology of GVHD including in-vivo and ex-vivo T-cell depletion alongwith methods of selective T-cell depletion, modulation of T-cell co-stimulatory pathways (checkpoints), enhancing regulatory T-cells (Tregs), targeting T-cell trafficking as well as cytokine pathways. Finally we highlight exciting novel pre-clinical research that has the potential to translate to the clinic successfully. We approach these methods from a pathophysiology based perspective as well and touch upon strategies targeting the interaction between tissue damage induced antigens and T-cells, regimen related endothelial toxicity, T-cell co-stimulatory pathways and other T-cell modulatory approaches, T-cell trafficking and cytokine pathways. We end this review with a critical discussion of existing data and novel therapies that may be transformative in the field in the near future as a comprehensive picture of GVHD prophylaxis in 2020. While calcineurin inhibitors remain the standard, post-transplant cylophosphamide originally developed to facilitate haploidentical transplantation is becoming an attractive alternative to traditional calcinuerin inhibitor based prophylaxis due to its ability to reduce severe forms of acute and chronic GVHD without compromising other outcomes, even in the HLA-matched setting. In addition T-cell modulation, particularly targeting some important T-cell co-stimulatory pathways have resulted in promising outcomes and may be a part of GVHD prophylaxis in the future. Novel approaches including targeting early events in GVHD pathogenesis such as interactions bvetween tissue damage associated antigens and T-cells, endothelial toxicity and T-cell trafficking are also promising and discussed in this review. GVHD prophylaxis in 2020 continues to evolve with novel exicitng therapies on the horizon based on a more sophisticated understanding of the immunobiology of GVHD.